Beyond Budgeting: Konsep Anggaran Alternatif Masa Depan - Wardayati, Siti Maria; Hidayatullah, Arif; Prahesti, Lina Rendra; Arafi, M. Wahyu Rahmadani Is (APSSAI, 2022)
This study intends to explore the concept and implementation of beyond budgeting in an era where environmental change is happening rapidly. The study adopts a systematic literature review from various articles and information from Internet sites. This study states that the dynamics of rapid environmental change have caused the traditional budget function to become suboptimal, so alternative budgeting methods with other methods have been implemented, for example, through the concept of better budgeting and beyond budgeting. Furthermore, the new concept developed is beyond budgeting because this concept provides freedom for capable people from top-down performance contracts with certain restrictions to obtain adequate resources to consistently increase the company's profitability.